Keunggulan kepengarangan Faisal Tehrani dari perspektif teksdealisme / Fauzi Hasan - Fauzi , Hasan (2019)
This study aims to analyze and assess the superiority of Faisal Tehrani's authorship based on his selected novels. The superiority gained put himself in his own level and distinguish from other authors. In order to achieve this goal, the study analyzed seven novels entitled Perempuan Politikus Melayu (2000), 1515 (2003), 1511H[Kombat] (2004), Surat-surat Perempuan Johor (2005), Tunggu Teduh Dulu (2008), Bahlut (2010) and Bagaimana Anyss Naik Ke Langit (2016). Research methodology applied in this paper was qualitative that analyzed text and fieldwork. The theory used in this paper is Textsdealisme theory introduced by Mana Sikana. This theory sets out four principles for analyzing superiority, namely the principle of presence, collision, consolidation, and individualism. All the principles of Textsdealisme theory were applied to assess the stage of Faisal Tehrani's excellence. Achievements of superiority divided into three levels, namely low (weak), partial (moderate) and high. In the principle of attendance suggested that research novels derive presence from experiences, adventures, assessments, readings and current issues. For the principle of collision showed a collision from the aspect of the theme, character, background, flow and storytelling technique. The principle of consolidation showed the strengthening of aspects of thinking, subject, character, mini-narrative issues, flow, storytelling techniques, backgrounds, use of facts and sources of support. The principle of individualism that built the identity of authorship were the aspect of subjectivity, individual style, individuality, and individual action. The study has found that there is another aspect that builds on the author's individualism, namely sensitivity, and creativity. The findings show that Faisal Tehrani achieved a high level of superiority based on research have been done on his novels. However, the level of superiority will change because it will be determined by his future works.